Performance analysis for indoor location determination. (29th July 2011) - Ji, Yiming
This work analyses theoretical localisation limits and proposes a precision bound to evaluate the performance of indoor systems under various configuration settings and environmental dynamics. By deploying a set of localisation systems in two different buildings, this study showed that database-based indoor systems perform slightly better than distance-based systems, and while it appears difficult to interpret the relationship between localisation performance and various environmental or configuration factors, the achievable precision of a localisation system for a given building is bounded and predictable. Thus this research provides a single standard criterion for the evaluation of various location determination systems.